Influence of Recycled Aggregate Quality on the Mechanical Properties of Concrete - Pavlu, Tereza; Boehme, Luc; Hajek, Petr (Communications - Scientific Letters of the University of Zilina, 2014)
The use of recycled construction and demolition waste - especially recycled concrete - as an aggregate for new concrete mixes, leads to saving of natural resources and helps to reduce the pressure on landfilling sites. Mostly the quality of recycled concrete is lower compared to standard concrete prepared with the same mix design. The reason for the drop in quality is mainly related to the quality of the recycled aggregate. The high water absorption of recycled aggregate has a negative impact of concrete mix workability and influences the water-cement ratio. This paper presents the effect of recycled aggregate quality on the physical and mechanical properties of concrete. Series of concrete with various replacement ratios of natural aggregate by recycled aggregate were prepared for this study. The obtained results confirm the potential use of developed recycling concrete made with local recycled aggregate in some applications in building construction. This can lead to environmental savings, especially reduction of primary resources use, embodied energy and embodied emissions.
Keywords: recycled aggregate; recycled concrete; construction and demolition waste; environmental savings